The Use of Computer-Based Image Analysis on Colour Determination of Liquid Smoked Trout (Oncorhynchus mykiss) Treated with Different Dry Salt-Sugar Mixtures - Zayde Ayvaz; Fikret Çakır; Hatice Gündüz; Mehmet Erdağ (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the changes in % yield, dry matter, ash, lipid, protein content, water activity, pH, total volatile basic nitrogen (TVB-N), total viable aerobic count (TVC), yeast and mold count, lactic acid bacteria (LAB), colour parameters and sensorial properties were analysed in rainbow trout (Oncorhynchus mykiss) exposed to either salt only or two different salt-sugar mixture treatments. For this purpose, three groups were formed. For the first, second and third group, fish samples were treated with only salt (S), salt and sugar blend (WS) and salt and brown sugar blend (BS), respectively. Then, the samples were vacuum packaged and stored at +4°C for 3 months. Overall, salt treatments, liquid smoking and cooking as well as storage generally caused remarkable changes in the parameters of interest. However, except for the sensory analysis, not a remarkable change was seen when the three groups were compared among themselves. The results of experienced panelists suggested that group BS samples had superior appearance, taste, odor and texture and therefore expected to be more preferred by the potential consumers.